397 Long-term follow-up after balloon expandable covered stents implantation for management of TAVI-related vascular access complications. (8th December 2021) - Maurina, Matteo; Regazzoli, Damiano; Condello, Francesco; Mangieri, Antonio; Stefanini, Giulio Giuseppe; Bongiovanni, Dario; Leone, Pier Pasquale; Baggio, Sara; Gasparini, Gabriele; Pagnotta, Paolo; Colombo, Antonio; Reimers, Bernhard
Abstract: Aims: Despite increasing experience and device innovation with transcatheter aortic valve implantation (TAVI), vascular complications are still a major problem and endovascular management is generally the first option. When stent implantation is required, self expandable (SE) stents are generally preferred over balloon expandable (BE) stents as they are more elastic and less compressible. However, BE stents support higher radial outward force, adhere to the vase lumen with greater precision and are less expensive. As no large registry reported data about stents BE alone in this setting, we report our experience with BE stents implantation to manage a vascular complication after TAVI. We believe that our work could be useful and possibly serves as a starting point for future research. Methods and results: We retrospectively collected baseline, procedural and follow-up data about 78 patients who were implanted with a BE stent to manage a vascular complication after TAVI. At a median clinical follow-up of 410 days (IQR: 66–1016 days), no percutaneous or surgical interventions were reported after discharge. No cases of symptomatic leg-ischaemia were reported and only one patient was symptomatic for claudication. Doppler follow-up (available for 25 patients; 32%) showed no cases of stent fracture or displacement. Conclusions: Our experience showed good acute and long-term results of BE covered stent implantation to manage a vascular complication after TAVI. It is possible that a greater radial outward force is a good choice in terms of hemostasis without necessarily being associated with stent deformation/fracture resulting in restenosis or further interventions. While present data may not be generalized, they may be useful to critically re-evaluate (and eventually reduce) the need of SE stents when treating femoral arteries bleedings.